# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+5 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}25 y^{\prime \prime }-20 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+13 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+\frac {5 y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }-24 y^{\prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+9 y^{\prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+\frac {25 y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }-12 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime }-5 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+\frac {5 y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }-9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}a \,x^{2} y^{\prime \prime }+b x y^{\prime }+c y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+4 x y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+\frac {5 y}{4} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-4 x y^{\prime }-6 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+2 x y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{2} y^{\prime \prime }+x y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}4 x^{2} y^{\prime \prime }+8 x y^{\prime }+17 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+3 x y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{4}+2 y = 0
\] |
✓ |
✓ |
|
\[
{}m y^{\prime \prime }+k y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-3 y = 3 \,{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 3 \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-3 y = -3 t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime } = 3+4 \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = t^{2} {\mathrm e}^{3 t}+6
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 2 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+4 y = 2 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = 2 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 3 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-4 y^{\prime }+y = 16 \,{\mathrm e}^{\frac {t}{2}}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }+3 y^{\prime }+y = t^{2}+3 \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 3 \sin \left (2 t \right )+t \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}u^{\prime \prime }+w_{0}^{2} u = \cos \left (w t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+4 y = 2 \sinh \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = \cosh \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = 2 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = t^{2}+3 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = t \,{\mathrm e}^{t}+4
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-3 y = 3 t \,{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 3 \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 4 \,{\mathrm e}^{-t} \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = 2 t^{4}+t^{2} {\mathrm e}^{-3 t}+\sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = t \left (\sin \left (t \right )+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = {\mathrm e}^{t} \cos \left (2 t \right )+{\mathrm e}^{2 t} \left (3 t +4\right ) \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+2 y = 3 \,{\mathrm e}^{-t}+2 \,{\mathrm e}^{-t} \cos \left (t \right )+4 \,{\mathrm e}^{-t} t^{2} \sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+4 y = 2 t^{2}+4 t \,{\mathrm e}^{2 t}+t \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = t^{2} \sin \left (2 t \right )+\left (6 t +7\right ) \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }+2 y = {\mathrm e}^{t} \left (t^{2}+1\right ) \sin \left (2 t \right )+3 \,{\mathrm e}^{-t} \cos \left (t \right )+4 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 3 t \,{\mathrm e}^{-t} \cos \left (2 t \right )-2 t \,{\mathrm e}^{-2 t} \cos \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime }-4 y = 2 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+7 x y^{\prime }+5 y = x
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 y = 3 x^{2}+2 \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+4 y = \sin \left (\ln \left (x \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \left \{\begin {array}{cc} t & 0\le t \le \pi \\ \pi \,{\mathrm e}^{-t +\pi } & \pi <t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = \left \{\begin {array}{cc} 1 & 0\le t \le \frac {\pi }{2} \\ 0 & \frac {\pi }{2}<t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \left \{\begin {array}{cc} A t & 0\le t \le \pi \\ A \left (2 \pi -t \right ) & \pi <t \le 2 \pi \\ 0 & 2 \pi <t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{4}+2 y = 2 \cos \left (w t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 2 \cos \left (w t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 3 \cos \left (w t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{8}+4 y = 3 \cos \left (\frac {t}{4}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{8}+4 y = 3 \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{8}+4 y = 3 \cos \left (6 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 2 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-2 y = 2 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y = 3 \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }-4 y^{\prime }+y = 16 \,{\mathrm e}^{\frac {t}{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \tan \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 3 \sec \left (2 t \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = \frac {{\mathrm e}^{2 t}}{t^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 2 \csc \left (\frac {t}{2}\right )
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+y = 2 \sec \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = \frac {{\mathrm e}^{t}}{t^{2}+1}
\] |
✓ |
✓ |
|